KESESUAIAN KURIKULUM SEKOLAH DASAR DENGAN TUNTUTAN PERKEMBANGAN SOSIAL DAN TEKNOLOGI - Nurrahmah, Hevi Dyah; Pramudita, Dhestya Praba; Septian, Zellina Hilda; Firga Rezhiana; Romi, Febryan Syah; Budiyono, Reisha Cahyarani; Delia Indrawati; Helda Kusuma Wardani (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Elementary school curricula must be flexible and adaptable to changes over time due to the quick development of social dynamics and technology. The Merdeka Curriculum has been designed to enhance flexibility, creativity, and 21st-century competencies; however, its implementation still faces various challenges. This literature study analyzes the alignment of the elementary school curriculum with social and technological developments by utilizing data from relevant scientific journals and research articles. The findings indicate that, although the curriculum has been designed to be adaptive, its implementation remains limited by factors such as teachers’ competencies, facilities, and support from the educational environment. Therefore, continuous adjustments are necessary to improve the curriculum’s alignment with ongoing social and technological changes. These adjustments can be achieved through improving teacher competencies, developing educational facilities, and strengthening collaboration between schools and the community, so that the elementary school curriculum becomes more effective in enhancing students’ knowledge and skills.